Investigating Customer Satisfaction of the Bakauheni-Palembang Toll Road - Dini Dwi Wulandary; Agung Kresnamurti Rivai; Rahmi Rahmi (Jambura Science of Management, 2022)
This study aims to determine the effect of service quality, E-WOM, and perceived value on customer satisfaction of the Bakauheni-Palembang Toll Road. This study uses quantitative methods. Data collection technique using a survey method with an instrument in the form of a questionnaire. The sample in this study amounted to 200 respondents who have used the Bakauheni-Palembang Toll Road at least twice in the last year. Use SPSS 22 version and Lisrel 8.8 SEM (Structural Equation Model) for technical data analysis to process and analyze research data. The results showed that service quality has no significant effect on E-WOM, service quality had no significant effect on customer satisfaction, the perceived value has a significant effect on E-WOM, perceived value has a significant effect on customer satisfaction, E-WOM has a significant impact on customer satisfaction, service quality has no significant effect on customer satisfaction through E-WOM, perceived value has a significant effect on customer satisfaction through E-WOM.